Upaya Meningkatkan Keterampilan Membaca Permulaan pada Anak Usia Dini Melalui Media Kartu Kata Bergambar - Pratiwi Rahmah Hakim (ABNA : Journal of Islamic Early Childhood Education, 2020)
The millennial era requires early childhood to be proficient and proficient in all aspects of learning, including proficiency in language. One language skill that is no less important is in the aspect of reading. The purpose of this study was to determine the teacher's efforts to improve pre-reading skills. This type of research is descriptive qualitative. The place of this research is in Kriwen Kindergarten, Sukoharjo District. The research period was from August 2019 to December 2019. Collecting data through observation, interviews and documentation. The results obtained in this study indicate that the efforts made by the teacher in improving initial reading skills through the use of picture word cards. With the application of these pictorial word cards students will find iteasier to spell words.